Oral intake of Streptococcus thermophilus improves knee osteoarthritis degeneration: A randomized, double-blind, placebo-controlled clinical study. Issue 4 (April 2020) - Lyu, Jia-Ling; Wang, Ting-Ming; Chen, Yen-Hao; Chang, Shu-Ting; Wu, Ming-Shiang; Lin, Yung-Hao; Lin, Yung-Hsiang; Kuan, Chen-Meng
Abstract: This preliminary clinical study demonstrates the possibility of a new species of probiotic for improvement of the degeneration of knee osteoarthritis (KOA). TCI633 ( Streptococcus thermophil us ) is a newly founded bacterium from human breast milk, and it is able to produce hyaluronate (HA) in gastrointestinal (GI) tract. A recent study has proved that TCI633 can substantially alleviate synovial tissue inflammation and cartilage damage in the animal models, but so far it has never been applied in clinical intervention. In this study, we recruited 80 subjects and conducted 12 weeks clinical trial to validate the efficacy of TCI633 for improvement of the progression of KOA. TCI633 could improve serum collagen type II C-telopeptide (sCTX-II) and serum C-reactive protein (sCRP) by 41.58% and 39.58%, respectively, after the study. The improvement rates for sCTX-II and sCRP in TCI633 group were 54% and 57%, respectively, at 12 weeks. Compared to the results of placebo, the indistinct improvement progresses of sCTX-II and sCRP might be caused by the uneventful distribution of K/L populations between the TCI633 and placebo groups, a short term of study period, and few recruited subjects. Moreover, the results of Western Ontario and McMaster Universities (WOMAC) questionnaires show that TCI633 might retard the progression and development of KOA after the trial. In brief, this preliminary research may provide an alternative approach to the improvement of KOA by probiotics although more detailed investigations should be conducted for solid conclusions. Abstract : Microbiology; Food Microbiology; Aging; Musculoskeletal System; Streptococcus thermophilius; probiotics; hyaluronic acid; Knee osteoarthritis